If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6a(a + -1b) + 2a(a + -1b) = 0 (a * 6a + -1b * 6a) + 2a(a + -1b) = 0 Reorder the terms: (-6ab + 6a2) + 2a(a + -1b) = 0 (-6ab + 6a2) + 2a(a + -1b) = 0 -6ab + 6a2 + (a * 2a + -1b * 2a) = 0 Reorder the terms: -6ab + 6a2 + (-2ab + 2a2) = 0 -6ab + 6a2 + (-2ab + 2a2) = 0 Reorder the terms: -6ab + -2ab + 6a2 + 2a2 = 0 Combine like terms: -6ab + -2ab = -8ab -8ab + 6a2 + 2a2 = 0 Combine like terms: 6a2 + 2a2 = 8a2 -8ab + 8a2 = 0 Solving -8ab + 8a2 = 0 Solving for variable 'a'. Factor out the Greatest Common Factor (GCF), '8a'. 8a(-1b + a) = 0 Ignore the factor 8.Subproblem 1
Set the factor 'a' equal to zero and attempt to solve: Simplifying a = 0 Solving a = 0 Move all terms containing a to the left, all other terms to the right. Simplifying a = 0Subproblem 2
Set the factor '(-1b + a)' equal to zero and attempt to solve: Simplifying -1b + a = 0 Reorder the terms: a + -1b = 0 Solving a + -1b = 0 Move all terms containing a to the left, all other terms to the right. Add 'b' to each side of the equation. a + -1b + b = 0 + b Combine like terms: -1b + b = 0 a + 0 = 0 + b a = 0 + b Remove the zero: a = b Simplifying a = bSolution
a = {0, b}
| (9b-8)-4(2b+1)=-3 | | -5n=4m+4 | | 4(5x+7)=-29+17 | | T-(2/3)=2t-(7/6) | | 6x-[3x-(5x-4y)]-6y= | | 4/5s^2-5t^2 | | 12x^2-12x+504=0 | | 7e^3x=987 | | y=-1/8x+9 | | -0.6x-0.9x-3=6 | | 8y=-x+9 | | 2+3(5-x)=-5+6x | | -a=40 | | 9x=y | | x/3-3=-7 | | 11x+21=120 | | (8y+30)-(2y+16)=-22 | | 5=y-6 | | 5p+5=11+4p | | 3x-1+x=9x+3+4 | | 8x^5/4x^3 | | 1/4x+1/8x=-9 | | 7z-29=-13+9z | | 0.1x=4.3 | | 3x-26=-20+6x | | z-3z=6z-2-z | | 20n-30=20-5n | | 3/4x+1/6+1/2x+4/5 | | 0.12y+0.08(y+2000)=1160 | | 3(x-6)=14-x | | 64*19= | | 0.3x^2-1.8x+0.3=0 |